Quantifying Tissue Properties of the Optic Radiations Using Strategically Acquired Gradient Echo Imaging and Enhancing the Contrast Using Diamagnetic Susceptibility Weighted Imaging - Jella, P.K.; Chen, Y.; Tu, W.; Makam, S.; Beckius, S.; Hamtaei, E.; Hsu, C.C.-T.; Haacke, E.M. (American Journal of Neuroradiology, 2021)
SUMMARY: Visualization of the optic radiations is of clinical importance for diagnosing many diseases and depicting their anatomic structures for neurosurgical interventions. In this study, we quantify proton density, T1, T2*, and susceptibility of the optic radiation fiber bundles in a series of 10 healthy control participants using strategically acquired gradient echo imaging. Furthermore, we introduce a novel means to enhance the contrast of the optic radiations using diamagnetic susceptibility weighted imaging.dSWIdiamagnetic susceptibility weighted imagingESSexternal sagittal striatumISSinternal sagittal striatumORoptic radiationSTAGEstrategically acquired gradient echoTAPtapetumHPFhigh-pass-filteredQSMquantitative susceptibility mapPDproton density